MICROBIOLOGICAL AIR QUALITY IN INTENSIVE NURSING WARDS, OF BRAWIlAYA HOSPITAL SURABAYA - Septia Anggraini; Erna Triastuti; Moh. Muchson (GEMA LINGKUNGAN KESEHATAN, 2013)
Intensive nursing rooms is known high risk zone in which the quality of air should bekept up to the highest standard because it may result in various health disorders. Thisresearch aims to discover the quality of air within the intensive nursing rooms of the BrawijayaHospital in Surabaya in 2013 through comparison with designated standards set forth inhealth ministry decree No. 1204/MENKES/SK/X/2004 re: health requirements of for hospitals.This descriptive research has been conducted at Brawijaya Hospital Surabaya in May2013. There were 11 rooms under study to be represented by air samples taken from 3rooms, i.e. Nusa Indah Room, Dahlia Room, and Tulip Room. The variables to be studiedamong others were microbiological quality of air as shown by number of germs, physicalmeasurements consisting temperature and humidity, assessment of room construction, densityof occupation, and purifying process.Results indicated that the highest number of germ before purifying process was 444CFU/m3 while at the time of patient visitation the number was 672 CFU/m3 meaning that theydid not comply to the requirements stated in health ministry decree no.1204/MENKES/SK/X/2004 which stated that the number of germs in children nursing room is200 CFU/m3 and adult nursing room is 200-500 CFU/m3• The highest temperature recorded atthe time before purifying process was 30°C and the humidity was 57%; while at the time ofpatient visitation the measurements indicated a temperature of 32°C and humidity of 58%.Density assessment has complied to the designated requirements: for a children nursing roomis 2 m2/bed and adult nursing room is 4.5 m2/bed. Pertaining to room and buildingconstruction of the intensive nursing ward that did not comply to the requirement was 60%while the purifying proces which did not comply with the requirements was 54%.Research concluded that number of germs in Nusa Indah Room at the time beforepurifying process and in Tulip Room at the time of patient visitation were clearly not complyingto the requirements. The suggestion included monitoring the quality of air on a regular basisin accordance with the health minister decree No. 1204/MENKES/SK/X/2004.Keyword: Mikrobiological, Air Quality, Intensif Nursing Wards